Family A DNA Polymerase Phylogeny Uncovers Diversity and Replication Gene Organization in the Virioplankton - Nasko, Daniel J.; Chopyk, Jessica; Sakowski, Eric G.; Ferrell, Barbra D.; Polson, Shawn W.; Wommack, K. Eric (Frontiers in Microbiology, 2018)
Shotgun metagenomics, which allows for broad sampling of viral diversity, has uncovered genes that are widely distributed among virioplankton populations and show linkages to important biological features of unknown viruses. Over 25% of known dsDNA phage carry the DNA polymerase I (polA) gene, making it one of the most widely distributed phage genes. Because of its pivotal role in DNA replication, this enzyme is linked to phage lifecycle characteristics. Previous research has suggested that a single amino acid substitution might be predictive of viral lifestyle. In this study Chesapeake Bay virioplankton were sampled by shotgun metagenomic sequencing (using long and short read technologies). More polA sequences were predicted from this single viral metagenome (virome) than from 85 globally distributed virome libraries (ca. 2,100 and 1,200, respectively). The PolA peptides predicted from the Chesapeake Bay virome clustered with 69% of PolA peptides from global viromes; thus, remarkably the Chesapeake Bay virome captured the majority of known PolA peptide diversity in viruses. This deeply-sequenced virome also expanded the diversity of PolA sequences, increasing the number of PolA clusters by 44%. Contigs containing polA sequences were also used to examine relationships between phylogenetic clades of PolA and other genes within unknown viral populations. Phylogenic analysis revealed five distinct groups of phages distinguished by the amino acids at their 762 (E. coli IAI39 numbering) positions and replication genes. DNA polymerase I sequences from Tyr762 and Phe762 groups were most often neighbored by ring-shaped superfamily IV helicases and ribonucleotide reductases (RNRs). The Leu762 groups had non-ring shaped helicases from superfamily II and were further distinguished by an additional helicase gene from superfamily I and the lack of any identifiable RNR genes. Moreover, we found that the inclusion of ribonucleotide reductase associated with PolA helped to further differentiate phage diversity, chiefly within lytic podovirus populations. Altogether, these data show that DNA Polymerase I is a useful marker for observing the diversity and composition of the virioplankton and may be a driving factor in the divergence of phage replication components.